(3YbGFO GdfSajs - (3GdfSaj, CHh MaU, fLe GdOjf, YeQ Hf eMeO CMeO, J (B537 (3g`s
(3ChdgG (B:s
(3HYO GdHSedI ; bGd Cgd GdMb (B: (3MbGFb GdCTjGA KGHJI hGdYde HgG eJMbb NdGaG ddShaSWGFjI Ke CSHGH GdYde ddNdb KdGKI (B: (3GdMhGS GdSdjeI hGdNHQ GdUGOb hGdYbd aGdMhGS NeS (B: (3GdSeY hGdHUQ hGdTe hGdPhb hGddeSs
(3BNQgG (B:s
(3hGdeLJgO bO jUjH hjNWF hQSd GdHTQ CaVd ef QSd GdedGFcI hQSd GdedGFcI CaVd ef YGeI GdHTQ hYGeI GdHTQ ef GdeDefjf CaVd ef YGeI GdedGFcIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B5 / 60s
(3eYLe GdeDdajf (B2 / 571s
(3cTa GdXfhf (B2 / 1145s
(3TPQGJ GdPgH (B4 / 115s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds